Streptococcal toxic shock syndrome in a patient with community-acquired pneumonia. Impact of rapid diagnostics on patient management. Issue 8 (17th August 2020) - Bagge, Kristian; Pedersen, Louise; Lisby, Jan Gorm
Abstract : Here we describe a community-acquired pneumonia with Streptococcus pyogenes, group A following a common cold caused by human metapneumovirus. The patient, a 58-year-old woman with no prior medical history, developed respiratory failure and multi-organ dysfunction caused by streptococcal toxic shock syndrome. The patient was admitted to the intensive care unit and treated with supportive care. The definitive diagnosis was made by BioFire FilmArray by Biomerieux (multiplex PCR) 12 h before positive blood culture, thus enabling the clinician to add clindamycin and intravenous immunoglobulin to the treatment. The patient was discharged fully recovered after 23 days. Streptococci group A is a rare pathogen of severe pneumonia and rapid diagnostics by syndromic testing, potentially performed in a near patient setting, is crucial for early implementation of targeted antimicrobial treatment.